Video Teleconferencing as a Tool for Science Education: Perceptions and Experiences of Tertiary Students in a Rural School in a Post-Pandemic Era - Pattung, Agustina (Jurnal Penelitian dan Pembelajaran IPA, 2024)
A qualitative study that tries to investigate perceptions and experiences of tertiary students regarding the application of video teleconferencing as an educational tool in science learning among students of a rural school post-pandemic. Interviews, focus group discussions, and observation revealed rich insights into how video teleconferencing technology could indeed be integrated in science courses. Various themes from research findings are brought out; among them is the influence video teleconferencing exerts on the level of students' engagement and their comprehension of the science curriculum. Others include approaches to pedagogy and challenges which face the students. To this end, students described having a more active engagement in science education via video teleconferencing, for it was interactive, thus allowing maneuverability around. However, they encountered challenges such as technical issues, accessibility barriers, and distractions. Nonetheless, video teleconferencing was found to be a crucial component of the educational process, which increases accessibility, broadens chances, and fosters the development of lifetime learning abilities. These results emphasize the necessity of resolving issues in order to maximize the efficiency of video teleconferencing in science instruction.